The management of students’ behavior in the classroom and its impact on their learning among teenagers and adults at CENIUES project. San Salvador, 2019 - Cruz Rivas, Guadalupe Griselda; Rodríguez Díaz, Gabriela Stefany (2024)
The following paper is product of the research Project “The Management of Students ́ Behavior in the Classroom and its Impact on their Learning among Teenagers and Adults at CENIUES Project. San Salvador, 2019.” In this research the mixed method was applied. The participants were one group of teenagers and one group of adults students from the Basic English Level at CENIUES Project. There were two teachers of the Basic English interviewed. The instruments were observation, interview, and survey. At the end of the researcher it was concluded that it does not matter if the teacher stabishes rules from the first day of classes, but if the students do not have values they will break all of them. Also, since education starts at home, and some students have problems with their family they will reflex those problems in the classroom. And finally, for professors it is difficult to deal with students who have emotional disorders because they do not have trainingin this area.